A machine learning model for real-time total nitrogen monitoring in Tampa Bay - Bo Yang; Yonggang Liu; Weiyi Tang; Jason A. Law; Robert H. Weisberg; Marcus W. Beck; Edward T. Sherwood; Thomas K. Frazer (Marine Pollution Bulletin, 2026)

Divergent effects of straw and biochar on soil carbon priming are depth-dependent in subtropical Moso bamboo forests - Zhenhui Jiang; Shaobo Zhang; Caixian Tang; Mouliang Xiao; Jiashu Zhou; Yu Luo; Tida Ge; Bing Yu; Jason C. White; Yongfu Li (Biology and Fertility of Soils, 2026)

Tillage changes transport and fate of microplastics in the agricultural environment - Binbin Wang; John Sloan; Hakyung Lee; Minkyoung Jung; Yinjie J. Tang; Young-Shin Jun; Martin Burstein; Jason H. Knouft (Agriculture, Ecosystems & Environment, 2026)

Crop management practices are more important for modern than past maize genotypes - Alejo Ruiz; Jason DeBruin; Tom Tang; Chris Zinselmeier; Jose L. Rotundo; Paige Oliver; Lucas Borras (Field Crops Research, 2026)

Task success in trained spiking neural network models coincides with emergence of cross-stimulus-modulated inhibition - Yuqing Zhu; Chadbourne M. B. Smith; Tarek Jabri; Mufeng Tang; Franz Scherr; Jason N. MacLean (Biological Cybernetics, 2026)
The neocortex is composed of spiking neurons interconnected in a sparse, recurrent network. Spiking activity within these networks underlies the computations that transform sensory inputs into appropriate behavioral responses. In this study, we train recurrent spiking neural network (SNN) models constrained by neocortical connectivity statistics and investigate the architectural changes that enable task-relevant, spike-based computations. We employ a binary state change detection task—an experimental paradigm used in animal behavioral studies. Our SNNs consist of interconnected excitatory and inhibitory units with connection probabilities and strengths modeled after the mouse neocortex and maintained throughout training and evaluation. Following training, we find that SNNs selectively modulate firing rates based on the binary input state, and that excitatory and inhibitory connectivity within and between input and recurrent layers adjusts accordingly. Notably, inhibitory neurons in the recurrent layer that positively modulate firing rates in response to one input state strengthen their connections to recurrent units with the opposite modulation. This push-pull connectivity—where excitation and inhibition are dynamically balanced in an opponent fashion—emerges as a key computational strategy and is reminiscent of connectivity observed in primary visual cortex. Using a one-hot output encoding yields identical firing rates to both input states, yet the push-pull inhibitory motif still arises. Importantly, this motif fails to emerge when Dale’s principle is not enforced during training, and task performance also declines.Furthermore, disrupting spike timing by a few milliseconds significantly impairs task performance, highlighting the importance of precise spike time coordination for computation in sparse networks like neocortex. The emergence of push-pull inhibition through task training in spiking models underscores the crucial role of interneurons and structured inhibition in shaping neural dynamics and spike-based information processing.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Biochar mitigates the suppressive effects of nitrogen deposition on soil methane uptake in a subtropical forest - Jiashu Zhou; Caixian Tang; Tony Vancov; Shenglei Fu; Yunying Fang; Tida Ge; Yanfei Dong; Yu Luo; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Agriculture, Ecosystems & Environment, 2026)

Biochar alleviates ammonium-induced suppression of methane uptake in a subtropical forest soil - Jiashu Zhou; Yanfei Dong; Caixian Tang; Zhenhui Jiang; Xinzhang Song; Mouliang Xiao; Hua Qin; Yunying Fang; Xiaokai Zhang; Tida Ge; Yu Luo; Shuokang Liu; et al. (Chemical Engineering Journal, 2025)

Nanozeolite-coupled biochar-based phosphorus fertilizer decreases soil N2O emissions in a subtropical Moso bamboo forest - Xinyong Sun; Shuokang Liu; Caixian Tang; Jiashu Zhou; Zhenhui Jiang; Chang Dong; Yu Luo; Tida Ge; Jason C. White; Yanjiang Cai; Bing Yu; Yongfu Li (Journal of Environmental Management, 2025)

Pliensbachian (Early Jurassic) deep-time peatland evolution in Northwest China driven by climate change - Lusheng Yin; Minfang Yang; Jing Lu; Xiaoxuan Wu; Xue Peng; Wanqing Wang; Maoyin Tang; Kai Zhou; Peixin Zhang; Longyi Shao; David P.G. Bond; Jason Hilton (International Journal of Coal Geology, 2025)

Nitrogen-induced suppression of methane uptake is alleviated by biochar in a subtropical forest soil - Jiashu Zhou; Shuokang Liu; Caixian Tang; Mouliang Xiao; Tida Ge; Yu Luo; Yanfei Dong; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Environmental Research, 2025)

Transformer-based approach to fault detection of chilled water systems: Insights from time and frequency domains - Jason Lin; Wei-Zhe Tang; Chia-Wei Tsai (International Journal of Refrigeration, 2025)

Sustained superiority of biochar over straw for enhancing soil biological-phosphorus via the mediation of phoD-harboring bacteria in subtropical Moso bamboo forests - Zhenhui Jiang; Tony Vancov; Yunying Fang; Caixian Tang; Wenyi Zhang; Mouliang Xiao; Xinzhang Song; Jiashu Zhou; Tida Ge; Yanjiang Cai; Bing Yu; Jason C. White; et al. (Forest Ecology and Management, 2025)

Simultaneous removal of nutrients and pharmaceuticals and personal care products using two-stage woodchip bioreactor-biochar treatment systems - Hongxu Zhou; Haribansha Timalsina; Shuai Tang; Sophie Circenis; Jason Kandume; Richard Cooke; Buchun Si; Rabin Bhattarai; Wei Zheng (Journal of Hazardous Materials, 2024)

Examining the nonlinear relationships between park attributes and satisfaction with pocket parks in Chengdu - Qi Tang; Jason Cao; Chun Yin; Jiawei Cheng (Urban Forestry & Urban Greening, 2024)

C-terminal residues of DNA polymerase β and E3 ligase required for ubiquitin-linked proteolysis of oxidative DNA-protein crosslinks - Jason L. Quiñones; Meiyi Tang; Qingming Fang; Robert W. Sobol; Bruce Demple (DNA Repair, 2024)

Maize straw increases while its biochar decreases native organic carbon mineralization in a subtropical forest soil - Jiashu Zhou; Shaobo Zhang; Junyan Lv; Caixian Tang; Haibo Zhang; Yunying Fang; Ehsan Tavakkoli; Tida Ge; Yu Luo; Yanjiang Cai; Bing Yu; Jason C. White; et al. (Science of The Total Environment, 2024)

Pyrogenic organic matter decreases while fresh organic matter increases soil heterotrophic respiration through modifying microbial activity in a subtropical forest - Jiashu Zhou; Shaobo Zhang; Dafeng Hui; Tony Vancov; Yunying Fang; Caixian Tang; Zhenhui Jiang; Tida Ge; Yanjiang Cai; Bing Yu; Jason C. White; Yongfu Li (Biology and Fertility of Soils, 2024)

Corrigendum to “Evaluating and mitigating the impact of systematic geolocation error on canopy height measurement performance of GEDI” [Remote Sensing of Environment, volume 291 (2023) 113571] - Hao Tang; Jason Stoker; Scott Luthcke; John Armston; Kyungtae Lee; Bryan Blair; Michelle Hofton (Remote Sensing of Environment, 2023)

Evaluating and mitigating the impact of systematic geolocation error on canopy height measurement performance of GEDI - Hao Tang; Jason Stoker; Scott Luthcke; John Armston; Kyungtae Lee; Bryan Blair; Michelle Hofton (Remote Sensing of Environment, 2023)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

Genome-first approach to rare EYA4 variants and cardio-auditory phenotypes in adults - Shadi Ahmadmehrabi; Binglan Li; Joseph Park; Batsal Devkota; Marijana Vujkovic; Yi-An Ko; David Van Wagoner; W.H. Wilson Tang; Ian Krantz; Marylyn Ritchie; Jason Brant; Michael J. Ruckenstein; et al. (Human Genetics, 2021)

Corrigendum to: Photosynthesis‐driven methane production in oxic lake water as an important contributor to methane emission - Marco Günthel; Isabell Klawonn; Jason Woodhouse; Mina Bižić; Danny Ionescu; Lars Ganzert; Steffen Kümmel; Ivonne Nijenhuis; Luca Zoccarato; Hans‐Peter Grossart; Kam W. Tang (Limnology and Oceanography, 2021)

Photosynthesis‐driven methane production in oxic lake water as an important contributor to methane emission - Marco Günthel; Isabell Klawonn; Jason Woodhouse; Mina Bižić; Danny Ionescu; Lars Ganzert; Steffen Kümmel; Ivonne Nijenhuis; Luca Zoccarato; Hans‐Peter Grossart; Kam W. Tang (Limnology and Oceanography, 2020)
Recent discovery of methane (CH 4 ) production in oxic waters challenges the conventional understanding of strict anoxic requirement for biological CH 4 production. High‐resolution field measurements in Lake Stechlin, as well as incubation experiments, suggested that oxic‐water CH 4 production occurred throughout much of the water column and was associated with phytoplankton especially diatoms, cyanobacteria, green algae, and cryptophytes. In situ concentrations and δ 13 C values of CH 4 in oxic water were negatively correlated with soluble reactive phosphorus concentrations. Using 13 C‐labeling techniques, we showed that bicarbonate was converted to CH 4 , and the production exceeded oxidation at day, but was comparable at night. These experimental data, along with complementary field observations, indicate a clear link between photosynthesis and the CH 4 production‐consumption balance in phosphorus‐limited epilimnic waters. Comparison between surface CH 4 emission data and experimental CH 4 production rates suggested that the oxic CH 4 source significantly contributed to surface emission in Lake Stechlin. These findings call for re‐examination of the aquatic CH 4 cycle and climate predictions.

Landslides after wildfire: initiation, magnitude, and mobility - Francis K. Rengers; Luke A. McGuire; Nina S. Oakley; Jason W. Kean; Dennis M. Staley; Hui Tang (Landslides, 2020)
In the semiarid Southwestern USA, wildfires are commonly followed by runoff-generated debris flows because wildfires remove vegetation and ground cover, which reduces soil infiltration capacity and increases soil erodibility. At a study site in Southern California, we initially observed runoff-generated debris flows in the first year following fire. However, at the same site three years after the fire, the mass-wasting response to a long-duration rainstorm with high rainfall intensity peaks was shallow landsliding rather than runoff-generated debris flows. Moreover, the same storm caused landslides on unburned hillslopes as well as on slopes burned 5 years prior to the storm and areas burned by successive wildfires, 10 years and 3 years before the rainstorm. The landslide density was the highest on the hillslopes that had burned 3 years beforehand, and the hillslopes burned 5 years prior to the storm had low landslide densities, similar to unburned areas. We also found that reburning (i.e., two wildfires within the past 10 years) had little influence on landslide density. Our results indicate that landscape susceptibility to shallow landslides might return to that of unburned conditions after as little as 5 years of vegetation recovery. Moreover, most of the landslide activity was on steep, equatorial-facing slopes that receive higher solar radiation and had slower rates of vegetation regrowth, which further implicates vegetation as a controlling factor on post-fire landslide susceptibility. Finally, the total volume of sediment mobilized by the year 3 landslides was much smaller than the year 1 runoff-generated debris flows, and the landslides were orders of magnitude less mobile than the runoff-generated debris flows.

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

The Properties of Cysteine-Conjugated Antibody-Drug Conjugates Are Impacted by the IgG Subclass - Amita Datta-Mannan; Hiuwan Choi; David Stokell; Jason Tang; Anthony Murphy; Aaron Wrobleski; Yiqing Feng (The AAPS Journal, 2018)

Differential methylation of the arsenic (III) methyltransferase promoter according to arsenic exposure - Matthew O. Gribble; Wan-yee Tang; Yan Shang; Jonathan Pollak; Jason G. Umans; Kevin A. Francesconi; Walter Goessler; Ellen K. Silbergeld; Eliseo Guallar; Shelley A. Cole; M. Daniele Fallin; Ana Navas-Acien (Archives of Toxicology, 2014)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Development, polymorphism, and cross-taxon utility of EST–SSR markers from safflower (Carthamus tinctorius L.) - Mark A. Chapman; John Hvala; Jason Strever; Marta Matvienko; Alexander Kozik; Richard W. Michelmore; Shunxue Tang; Steven J. Knapp; John M. Burke (Theoretical and Applied Genetics, 2009)